PANDUAN PEMBELAJARAN MIKRO BAGI DOSEN DAN MAHASISWA - Hasnawati; Aulia Evawani Nurdin (Universitas Negeri Makassar, 2023)
The aim of this research is to solve the problem of lecturers and students regarding the lack of microteaching guides at the Faculty of Art and Design, Makassar State University. Specifically, this research aims to develop a valid micro-learning guide for lecturers and students at the Faculty of Art and Design, Makassar State University. This type of research is research and development (R&D), is to develop microteaching learning guidelines. The development research model developed was adopted from the model developed by Thiagarajan, is to the Four-D model (Define, Design, Develop, and Disseminate). The Define stage is analyzing the needs of lecturers and students for microteaching learning. The analysis is carried out by observing and reviewing the needs of lecturers and students in microteaching learning, as well as reviewing literature related to microteaching. Design stage (design), after analyzing needs, the next step is to design a form of guide by making a storyboard, arranging the material included in the guidebook, creating learning scenarios, and creating assessment guides in microteaching learning. Develop stage (development), this stage is the stage of validating the micro learning guide that has been developed. and the Disseminate stage, the stage where the guidelines that have been developed are distributed to lecturers who teach microteaching courses and to students who program the courses. The number of validators involved in this research was two validators. Each one material expert and one media expert. Data collection techniques were carried out using observation, interviews, questionnaires and documentation techniques. Data analysis techniques were carried out using qualitative and quantitative descriptive analysis techniques. The research results show that the development of the microteaching guide went through four stages and was carried out in accordance with the research and development model developed by Thiagarajan, namely Define, Design, Develop and Disseminate. The microteaching guide for lecturers and students has been declared suitable for use in microteaching at the Faculty of Art and Design, Makassar State University.